Knowledge, self-efficacy, satisfaction and self-confidence of nursing students for stoma care using active learning methodologies: a quasi-experimental study of three arms - Abselam-Ali, Karima; Capilla Díaz, Concepción; Reina Prego , Rocío; Parra González, María Elena (Investigación y Educación en Enfermería, 2025)
Objective. To assess knowledge about stoma care in relation to the level of learning methods and to measure students’ self-confidence, satisfaction and self-efficacy with the training received using different learning methods including simulation. Methods. A quasi-experimental study of three arms, with pretest and post-test design in third-year nursing students during the academic year 2022-2023. Group A received traditional teaching methods and low-fidelity simulation, group B received traditional teaching methods and high-fidelity simulation, and group C received active learning methods and high-fidelity simulation. Results. Significant differences were found in 14 of the 15 NOC indicators measured between groups. Self-efficacy showed significant differences between the different groups (p<0.001) after the intervention. For satisfaction and self-confidence, there were significant differences (p<0.001) observed between the different fidelity groups). Conclusion. This study found that simulation improved the level of knowledge regarding ostomies and had a positive impact on satisfaction and self-confidence in all three intervention groups, with significantly higher results among participants in Group C (active learning methods and high-fidelity simulation).